An Evaluation of Core Competence on Knowledge Management for Elementary Schools’ Teachers: A Case Study of Remote Rural Area in Taiwan - Ya-Ching Yeh; Chia-Chun Hsiao . (Journal of Education and Vocational Research, 2012)
In the knowledge economy era, teachers’ core competencies for knowledge management have an important impact on the development of school education. It is an important issue to explore how to evaluate core competencies of knowledge management for elementary schools’ teachers. This requires a thorough investigation to gain core competencies. Hence, the main purpose of this paper is to present a Matrix Analysis (MA) approach for evaluating core competencies of knowledge management and to describe the applications of the MA approach for elementary schools’ teachers. An empirical analysis is performed to demonstrate the computational process of the MA approach adopted by this paper. Study results show that eleven core competencies are identified. They are ‘finding problems,’ ‘flexibility,’ ‘interpersonal communication,’ ‘oral communication skills,’ ‘knowledge selection,’ ‘activities recording,’ ‘knowledge application on work planning,’ ‘research data application,’ ‘transforming knowledge into concrete actions,’ ‘interpreting results,’ and ‘judging knowledge value,’ respectively. It is suggested that more attentions should be paid to exploit these core competencies effectively and then develop the solutions, which should continuously strengthen the perspective of teachers in order to obtain the competitive advantages in the future.